Deadbeats or losers: Discretionary male parental investment can make females less choosy. (7th June 2017) - Meacham, Frazer; Getty, Thomas
Highlights: With biparental care, mate preferences cannot be disentangled from PI decisions. Females may use a males attractiveness to gauge his likelihood of providing care. Greater variation among males due to PI decisions leads to lesser female choosiness. When males adjust parental investment, females mate with low-quality males more often. Abstract: Two of the most important reproductive decisions that animals face are how to choose mates and how to invest in offspring. In species where both males and females provide offspring care, these selection pressures will often be reciprocally intertwined: mate preferences may depend on parental investment patterns while parental investment patterns may depend on mate preferences. We describe and analyze a mathematical model of this interaction, in which females can choose amongst males who have high attractiveness or low attractiveness, while males can decide whether to provide offspring care. We compare the case where males decide whether to provide care to the cases where males always provide care and where they never provide care. For a wide range of parameter settings, we find that when males decide whether to provide care, females are selected to be less choosy. This reduction in female choosiness occurs even though discretionary male care leads to greater variation among males in their offspring output. This finding contrasts with previous theoretical studies, and is driven by our assumption that males can decide whether to help provide care after mating occurs. Our results show how the interdependencies between mate choice and parental care can generate outcomes that can only be understood by considering both processes simultaneously.